Effects of COVID-19 Pandemic on the Treatment Management of ST-elevation Myocardial Infarction - Hassan Shahbazi; Neda Mahdavifar; Ali Asghar Jesmi (Mashhad University of Medical Sciences, 2022)
Background: The outbreak of coronavirus disease 2019 (COVID-19) in early 2020 has affected reperfusion time in patients with ST-segment elevation myocardial infarction (STEMI) across the globe.Aim: The present study aimed to assess the effect of the COVID-19 pandemic on the treatment management of STEMI.Method: This quantitative cross-sectional descriptive-analytical study investigated medical records of all patients (n=279) with STEMI who were consecutively admitted to Heshmatieh Hospital in Sabzevar city and underwent Primary Percutaneous Coronary Intervention (PPCI) in the last 9 months of 2019 (from April to December) as "Pre-pandemic group" (n=161) and the same period in 2020 as "post-pandemic group" (n=118). The data collection tools were a demographic information form and a checklist for recording treatment information.Results: The average times from the symptom onset to first medical contact (FMC) and from FMC to the commencement of PPCI were significantly increased in the post-pandemic group, compared to those in the pre-pandemic group (870.50±1397.48 versus 348.80±399.20 min and 73.23±91.87 versus 52.68±27.46 min, respectively). The mean length of stay was reduced after the intervention in the post-pandemic group. Despite the reduction in the number of STEMI patients' referrals in the post-COVID-19 pandemic period, the comparison of the referral of patients by month showed no significant difference between the two study groups before and after the COVID-19 pandemic.Implications for Practice: The COVID-19 pandemic caused treatment delay and reduced hospital stay among STEMI patients. The results of this study can be used to inform the community and better manage time-dependent diseases, such as STEMI, in the future.